Evaluation of intoxication caused by post-emerging herbicides in cassava culture in two times of application - Machado Filho, Gilberto Coutinho; Santos, Mauro Gomes; Pachoute, Julner; Heinrich, Jéssica Dayane; Ribeiro, Rafaela Rodrigues; Santos, Manoel Mota (Acta Iguazu, 2020)
This study aimed to evaluate the selectivity of post-emergent herbicides in cassava in two application times. The experiments were carried out in a greenhouse at the Federal University of Tocantins - UFT, Campus Gurupi. The experimental designed was completely randomized arranged in a 5x2 factorial scheme, composed by the combination of 5 herbicide molecules with different mechanisms of action (mesotrione, carfentrazone-ethyl, chlorimuron-ethyl, nicosulfuron and imazethapyr) applied in two seasons, 30 and 45 days after emergence (DAE), with four repetitions. The cultivar used was “Cacau melhorada”. The visual intoxication of the culture was evaluated. The results obtained were subjected to analysis of variance, by the F test, with the averages analyzed statistically by the LSD mean test, at 5% probability. The treatments based on mesotrione, and chlorimuron-ethyl were not toxic to the culture, promoting results similar to those observed for control. There were differences in the level of tolerance to the studied herbicides, between the times of application of the herbicides.